VD_FINDINFO 163/2009/PMR vom 13. November 2009 - VD Tribunal cantonal (2009)
CAUTIONNEMENT, FORME AUTHENTIQUE, FORME ET CONTENU, VICE DE FORME | 492 CO, 493 CO, 496 CO, 499 CO, 500 CO, 501 CO, 123 al. 4 LNo, 58 LNo, 69 LNo